TRANSFORMATIONAL LEADERSHIP STRATEGY IN STRENGTHENING MADRASAH CULTURE AND IMPROVING THE QUALITY OF EDUCATIONAL SERVICES - Budiyanto Budiyanto; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Strengthening madrasah culture has become an urgent necessity amid increasing public demands for the quality of Islamic educational services. Many madrasahs face challenges in establishing a consistent, adaptive, and service-oriented culture, thereby requiring a leadership approach capable of driving change in a visionary and participatory manner. The urgency of this study lies in the need for an implementative model of transformational leadership that can strengthen madrasah culture while simultaneously improving the quality of educational services in a sustainable way. This study aims to describe the implementation of the principal's transformational leadership strategies in strengthening madrasah culture and to analyze their contribution to improving the quality of educational services. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques through source and method triangulation. The findings reveal that the madrasah principal implemented transformational strategies through inspirational motivation, individualized support, reinforcement of the madrasah's cultural vision, and the strengthening of collaboration. These strategies were effective in fostering a religious, disciplined, and service-oriented madrasah culture, which in turn contributed to improvements in both academic and non-academic educational services. The findings confirm that transformational leadership serves as a strategic approach to developing a quality-oriented madrasah culture. This study highlights the importance of visionary leadership as a fundamental foundation for enhancing the quality of educational services in madrasahs.